Mediation & conference programs in the federal courts of appeals : a sourcebook for judges and lawyers - Niemic, Robert J., 1950- (Federal Judicial Center, 2006)
Updated edition of the original 1997 sourcebook, a guide on mediation and settlement conference programs in all 13 federal courts of appeals.